Numerical modeling of the impact of projectiles on metal structures - Spasić, Dragoljub M. (Vojnotehnički glasnik / Military Technical Courier, 2017)
This paper describes the numerical modeling of impact damage caused by impacts of projectiles on metal structures and the experimental results of impacts of projectiles of different shapes on metal structures. The experiments were carried out by the impact of projectiles on metal barriers of steel and aluminum of different thicknesses with the change in the impact speed of projectiles. In order to make the effects of experimental impact simulations as close as possible to real ones, the missile impacts are varied to match the average and limit speeds of impacts of projectiles that break obstacles. The obtained experimental results coincided well with the real effects on metallic obstacles and similar conducted tests from foreign literature.
Keywords: aircraft; aircraft structure; impact; impact damage; modeling; missile; bullet projectile; penetrator; projectile penetration; penetration; ballistic protection